Pengaruh Kepemimpinan Terhadap Kinerja Dalam Sudut Pandang Pencapaian Key Performance Index (KPI) di Perusahaan Swasta Aceh - Rahmat Arfan; Desy Puspita; Fahmi Arfan (Politeknik Kutaraja, 2020)
The purpose of this research to find the effect of leadership include the leadership prioritize ethics, conflict resolution, and motivate employee performance, with quantitative method through questioner as tools and internal data from company relating to employee performance which is, in this case, using Key Performance Index (KPI) value as employee incentive. From analysis is found their leadership has influence simultaneously in increasing employee performance at a moderate level on R regression at 0.436 with increasing performance at 40%.